Rearing juvenile brown Salmo trutta (L.), and rainbow trout Oncorhynchus mykiss (Walbaum), in earthen ponds with and without an induced current. Issue 1 (2nd January 2021) - Reiser, Stefan; Sähn, Niko; Pohlmann, Dominique M.; Willenberg, Marc; Focken, Ulfert
ABSTRACT: Because moderate sustained exercise enhances growth in salmonids, we investigated whether paddle-wheel aerators (PWAs) used to provide juvenile brown and rainbow trout with conditions for sustained swimming can increase growth. On site a commercial farm, earthen ponds were provided with PWA and flow patterns recorded or ponds left without PWA. Growth was determined periodically and proximate body composition analyzed at 111 (rainbow trout) and 169 (brown trout) days. The PWA created circular flow patterns with a range of current speeds. First results show that brown trout reared with current had higher protein and lower fat. Rainbow trout reared with current had higher ash, lower fat, and lower energy. The current affected growth in weight of rainbow trout, while no effects on growth were observed in brown trout. PWA can also be used to create a circular flow pattern, allowing for volitional exercise at no or minor additional costs.